A symmetric enforcement of good faith provisions: a systematic review of contractual remedies for weaker parties in common law systems - Nurarafah Nurarafah; Sulaiman Sulaiman; Husni Husni (Lentera Negeri, 2026)
This study aims to deconstruct the paralysis of the corrective function of objective good faith when confronted with exploitative boilerplate clauses. To distinguish its contribution from decades of conventional, descriptive-sociological research on contractual imbalance, this doctrinal-conceptual inquiry anchors its analytical structure by integrating Ian Macneil’s Relational Contract Theory to dissect the social dimensions of contracts, alongside John Rawls’s Theory of Distributive Justice to evaluate the moral legitimacy of contractual exchanges. Moving beyond generic literature reviews, this study employs a rigorous Meta-Doctrinal Thematic Synthesis, selecting legal literature and jurisprudence based on strict inclusion criteria: the evolution of the abuse of circumstances doctrine within civil law systems, and Indonesian Supreme Court precedents on the invalidation of exculpatory clauses over the past decade (2016–2026). Based on strict inclusion and exclusion criteria targeting the implied covenant of good faith, unconscionability, and algorithmic duress, a definitive legal corpus of 42 specialized sources (33 peer-reviewed journal articles and 9 landmark appellate precedents) was extracted and analyzed. The analytical synthesis uncovers a highly specific doctrinal gap: contemporary common law jurisprudence suffers from systemic stagnation by restricting the operability of good faith to a passive interpretive rule or binding unconscionability to a rigid, formation-stage audit. Crucially, the evidentiary basis demonstrating the weak implementation and judicial paralysis of these remedies is derived directly from a structural analysis of Appellate Case Law across Key Common Law Jurisdictions, exposing a fragmented judiciary that routinely retreats into formalistic positivism and prioritizes literal text over substantive equity. As a distinct theoretical intervention, this paper proposes a Model of Progressive Judicial Intervention Based on Asymmetric Equity, providing the necessary dogmatic legitimacy for common law judges to look past formal compliance, penetrate unconscionable exculpatory terms, and actively reconstruct remedies to restore relational equilibrium during the contractual performance stage